ISPC Commentary on the Proposal for CRP3.5 - October 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the Proposal for CRP 3.5: Grain Legumes.